Faut-il continuer à faire de l’analyse de discours? - Reboul, Anne; Moeschler, Jacques (HERMES - Journal of Language and Communication in Business, 2017)
This paper is concerned with the legitimacy of discourse analysis. We intend to show here that discourse analysis rest on a highly debatable hypothesis and that the notion of coherence, which is closely associated with discourse analysis, is, at best, a pre-scientific notion. We will try to show that a reductionist approach to discourse would be both more scientifically sound and more efficient. We will, finally, outline an alternative view of discourse and coherence.